Nurturing the Self: How Interpersonal Relationships Foster Individual Development - Adelia Fristiana Putri; Mayang Ayu Angelita Sari; Rizky Akbar Dwi Alvaridzi (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2023)
The purpose of this study is to find out how interpersonal relationships can foster individual self-development. The research method uses a qualitative approach with a literature review through research searches with the selected keywords, namely